Effect of silver-containing agents on the ultra-structural morphology of dentinal collagen. Issue 7 (July 2020) - Sayed, Mahmoud; Hiraishi, Noriko; Matin, Khairul; Abdou, Ahmed; Burrow, Michael F.; Tagami, Junji
Abstract: Objective: This study investigated the effect of silver diammine fluoride (SDF), nano-silver (AgNPs) and nano-silver/potassium fluoride (AgNPs/KF) on the morphology of dentin collagen and color staining on the dentin. Also, we investigated the anti-caries properties in terms of anti-bacterial effects and potentiality of dentin remineralization at collagen level. Methods: Dentin specimens obtained from bovine tooth roots were finished with #2000 SiC and sonicated for 5 min. Specimens were divided into two main groups: sound and demineralized dentin. Each group was subdivided into five subgroups according to treatment solution: control (no treatment), SDF, nano-silver (AgNPs), AgNPs/KF and KF. Specimens were analyzed using transmission electron microscope (TEM), spectrophotometer, scanning electron microscope (SEM) and antibacterial test. Repeated Measures ANOVA was used for statistical analysis of color change while one-way ANOVA was used for CFU analysis. Results: Regarding color change, SDF showed the highest values while the other groups exhibited insignificant changes. SDF showed alteration in the collagen fibrils while the other groups showed normal intact fibrils. Regarding antibacterial activity, SDF and AgNPs/KF showed the greatest antibacterial effect. Significance: SDF altered the dentin collagen morphology and inferior ethetics, but still providing intrafibrillar remineralization. Nano-silver fluoride preparations (AgNPs/KF) can be an alternative material for SDF as it can preserve the dentin collagen, showing no color change overtime, and provide a high anti-caries property including intrafibrillar remineralization with a significant anti-bacterial effect.